Analysis of window parameters and shading strategies in buildings in hyper-arid desert coastal climates: a case study for Kuwait - Ahmad Edbais; Mokarram Hossain (Discover Sustainability)
Abstract The construction sector faces numerous environmental issues, such as natural resource depletion, greenhouse gas (GHG) emissions, air pollution, and human-caused global warming, to mention a few. The energy consumption in the building sector in Kuwait is increasing due to its hot climate, in which a large part of Kuwait’s total electricity consumption comes from residential buildings due to its high energy usage per capita and its hot climate. The main reason for this consumption is the refrigeration loads and air conditioning. This study investigates the impacts of window parameters (window-to-wall ratio (WWR) and glazing type), shading devices, and building orientation on the energy and daylighting performance of residential buildings in Kuwait. The research addresses the challenge of achieving energy-efficient and sustainable designs in hot climates where cooling demands are significant. Using DesignBuilder software, this research analysed annual energy consumption, energy use intensity, and daylight factors (average and maximum) to evaluate these parameters. Results reveal that Dbl Clr 6mm/6mm Air as glazing type, a 1 m projection overhang as a shading device, and 20% of WWR reduced annual energy consumption by 16.55% while maintaining adequate daylight levels. Additionally, a comparative analysis of a modified design versus a base model demonstrated significant energy savings in both Kuwait City and Sabah Al Ahmad. These findings provide actionable insights for architects and policymakers aiming to enhance building sustainability in the Cooperation Council for the Arab States of the Gulf (GCC) region.